2002
DOI: 10.1002/dvdy.10144
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of anterior segment development by TGF‐β1 overexpression in the eyes of transgenic mice

Abstract: Previous experiments showed that transgenic mice expressing a secreted selfactivating transforming growth factor (TGF) -␤1 did not show a phenotype in the lens and cornea until postnatal day 21, when anterior subcapsular cataracts, sporadic thickening of the corneal stroma, and thinning of the corneal epithelium were noted (Srinivasan et al., 1998). To examine the effects of higher concentrations of TGF-␤1 on the lens and cornea, we constructed transgenic mice harboring the strong, lens-specific chicken ␤B1-cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 66 publications
1
49
0
Order By: Relevance
“…Their data suggest that Pax6 is necessary for epithelial stratification; however, it is unclear if an environmental cue is required to stimulate the action of Pax6 in association with eyelid opening. Other factors that have been demonstrated to be involved in corneal development are TGF-β1 (Flugel-Koch et al, 2002), notch1 (Nicolas et al, 2003), TGF-α (Reneker et al, 2000), the forkhead/winged-helix gene (Kidson et al, 1999), and IκB kinase α (Yoshida et al, 2000). Intriguingly, both overexpression of TGF-α and deletion of forkhead lead to the lack of an endothelial cell layer.…”
Section: A B C D E F G H Regulation Of Gene Expression Associated Witmentioning
confidence: 99%
“…Their data suggest that Pax6 is necessary for epithelial stratification; however, it is unclear if an environmental cue is required to stimulate the action of Pax6 in association with eyelid opening. Other factors that have been demonstrated to be involved in corneal development are TGF-β1 (Flugel-Koch et al, 2002), notch1 (Nicolas et al, 2003), TGF-α (Reneker et al, 2000), the forkhead/winged-helix gene (Kidson et al, 1999), and IκB kinase α (Yoshida et al, 2000). Intriguingly, both overexpression of TGF-α and deletion of forkhead lead to the lack of an endothelial cell layer.…”
Section: A B C D E F G H Regulation Of Gene Expression Associated Witmentioning
confidence: 99%
“…The authors in that study have also speculated that in the TGFα and EGF transgenic mice, over stimulation of the TGF receptor in the corneal mesenchymal cells may have inhibited the TGFB/SMAD signaling pathway, which is essential for corneal endothelial specification and differentiation [15]. Several studies have shown that TGFB signaling appears to be essential for the formation of normal cornea during early eye development [36,37,38]. The TGFB super-family of secreted signaling molecules has an influence on several biological processes including: cell proliferation, cell differentiation, cell death, bone morphogenesis and wound repair [16].…”
Section: The Role Of Cadherins In Neural Crest Developmentmentioning
confidence: 99%
“…Their corneas were thickened. The transgenic corneal stroma was vascularized and densely populated by star-shaped cells indicating that the stromal cells retained a mesenchymal phenotype [38].…”
Section: The Role Of Cadherins In Neural Crest Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that TGF-␤ signaling can regulate the specification of the cranial neural crest and the establishment of the normal ocular anterior segments. Reduction of TGF-␤ signaling is linked to the human disorder Axenfeld-Rieger anomaly by regulating Pitx2 at the late embryonic stage (20,(51)(52)(53). However, in Smad7 mutant embryos, the broadened optic disc appears only for a short time.…”
Section: Smad7 In Eye Developmentmentioning
confidence: 99%